If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 2L + (10) 12 = 2L + 10 Reorder the terms: 12 = 10 + 2L Solving 12 = 10 + 2L Solving for variable 'L'. Move all terms containing L to the left, all other terms to the right. Add '-2L' to each side of the equation. 12 + -2L = 10 + 2L + -2L Combine like terms: 2L + -2L = 0 12 + -2L = 10 + 0 12 + -2L = 10 Add '-12' to each side of the equation. 12 + -12 + -2L = 10 + -12 Combine like terms: 12 + -12 = 0 0 + -2L = 10 + -12 -2L = 10 + -12 Combine like terms: 10 + -12 = -2 -2L = -2 Divide each side by '-2'. L = 1 Simplifying L = 1
| 56=w^2+6 | | 0.25x+0.2y=350 | | 988()=1234 | | x(x+5)=-150 | | x+7=3-x | | 2y+2+10y-2=90 | | 1Dwight+2x= | | 3(m-3)=0 | | 7m-2=0 | | 11x-5x+6x=168 | | -73+29= | | 2x+11=3x+11 | | 7ab(a+5b+ab-6^2)= | | 6z+18=z | | 2(4a+5)=1.8a-3 | | 2(5-4x)=-46 | | 29-9x=-5(7x+2)-5(-4-5x) | | 2x+11=2x-19 | | -8m-24=24 | | 5-2(y-5)=267 | | y+6n=6n+5 | | 40x=60y | | 4z+11=2z+7 | | 5y+6=-y+24 | | 42-14x=-5(6x+2)-5(-8-3x) | | 2(3a+1)=12+2(4a+3) | | 8-5x-4=-6x+6 | | 3m-4=20 | | 25*x^2-16*x^2= | | Y+14=10 | | x^0+1=0 | | 14x-12+30=4 |